Development of reversed-phase HPLC method for purity assessment of aryl porphyrins and their metal complexes - Ujagare, Ashish Mohan; Uzagare, Matthew C.; Ghogare, Bhausaheb N.; Gupta, Lokesh Kumar; Wadgaonkar, Prakash P.; Patil, Vishwanath R.; Donde, Kamini J. (SSC Plus, 2025)
A gradient reversed-phase HPLC method was developed for in-process monitoring of the formation of aryl porphyrins and their corresponding metallo-aryl porphyrins. The method also proved effective for determining their quantitative purity. Optimal results achieving proper peak shape and separation of peaks in the chromatogram were obtained using C8 column and gradient of acetic acid-water and acetonitrile. The detector wavelength was selected for simultaneous detection of starting materials and products for in-process analysis for conversion of aryl aldehydes to corresponding tetraaryl porphyrins at 254 nm and metallo-aryl porphyrins formation from tetraaryl porphyrin at 413 nm, respectively; while the purity of products could be determined at 413 nm. The developed method is efficient, versatile, accurate, and easy to carry out and could serve as a handy tool for the reaction monitoring and determination of purity in the processes development of synthetic porphyrins and metalloporphyrins.